“Safety is just a thing men take for granted”: Teaching a Spatial Vocabulary of Equality to Architecture Students - Keddy, Karen (Atlantis, 2015)
The focus of this paper is to present a method of teaching architecture students how to learn from conducting a socio-spatial analysis in order to design a safe and secure built environment. This paper illustrates the connections between the learning objectives of a multi-part assignment and issues of citizenship, inclusivity, and equity.